2002
DOI: 10.1080/08039480260389361
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral activation or inhibition during emotional stress--implications for exercise habits and emotional problems among young females

Abstract: According to the defense-defeat model of stress, the defense reaction is associated with behavioral activation and the defeat reaction with behavioral inhibition. The aim of this study was to investigate the associations of stress-induced changes of physical activity to certain psychological and behavioral problems among young females. A random sample of 726 females, aged 18-23 years, responded on a self-report questionnaire. Groups were defined by the given response on an item addressing changed levels of phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 7 publications
1
17
0
Order By: Relevance
“…Since this time, research designs have varied widely and have extended to include qualitative [171-179], retrospective [77, 180-183], prospective [17, 20, 184-192], and experimental work [193], although most studies are cross-sectional [143, 194-196]. Likewise, studies have narrowed from the examination of stress on the wider scope of health behaviors to a specific focus on the effects of stress on PA and exercise.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since this time, research designs have varied widely and have extended to include qualitative [171-179], retrospective [77, 180-183], prospective [17, 20, 184-192], and experimental work [193], although most studies are cross-sectional [143, 194-196]. Likewise, studies have narrowed from the examination of stress on the wider scope of health behaviors to a specific focus on the effects of stress on PA and exercise.…”
Section: Resultsmentioning
confidence: 99%
“…Speaking to the point of positive influences of stress, 29 studies found that stress predicts an increase in PA behavior [3, 17, 81, 164, 168, 171, 172, 175, 183, 251, 253, 254, 256, 259, 262, 264, 267, 269, 278-280, 313-320], ten of which were prospective (see above). Other studies found trends in this direction [169, 191].…”
Section: Resultsmentioning
confidence: 99%
“…It may be a function of the general coping style of the nurses interviewed. As an example, under conditions of stress, those with a rigid coping style may be more inclined to increase physical activity behaviour [54]. …”
Section: Discussionmentioning
confidence: 99%
“…A participant was classified as physically active if they regularly participated in sports during leisure time ≥ 1 hour/ week in either season. Difficulties initiating and maintaining sleep were assessed using a section of the Uppsala Sleep Inventory (USI) (Seigel et al, 2002). Two separate three-category questions were asked "Do you have trouble falling asleep?"…”
Section: Sociodemographic Parametersmentioning
confidence: 99%